ANALISIS PERAN LEMBAGA KEUANGAN NON-BANK SYARIAH DALAM PENGUATAN EKONOMI ISLAM DI INDONESIA - AHMAD AGUNG FAUZAN; DIAN MITHA PERMATASARI; RAFI WILDAN AR-RAZAN; RINI PUJI ASTUTI (Universitas Islam Negeri Imam Bonjol Padang, 2025)
AbstractAn in-depth analysis of Islamic insurance, lending, and pawning plays a vital role in the development of the Islamic economy. Islamic insurance offers protection against risks in accordance with Sharia principles, providing a sense of security for the public in the face of uncertainty. Meanwhile, lending and pawning are effective solutions for increasing financial access, especially for individuals and small businesses. These three elements complement each other in forming a fair and transparent financial system. However, challenges such as a lack of public understanding and inadequate regulations need to be addressed to maximize the sector's potential. This study aims to explore various aspects of these three components and provide strategic recommendations for the development of Islamic finance. Thus, it is hoped that this sector's contribution to supporting economic stability and community empowerment will be strengthened.Keywords: Islamic Insurance, Lending, Pawning, Islamic Economics, Financial Stability.